Telomere length regulation during postnatal development and ageing in Mus spretus - Coviello-McLaughlin, Gina M.; Prowse, Karen R. (Nucleic acids research, 1997)
Telomere shortening has been causally implicated in replicative senescence in humans. To examine the relationship between telomere length and ageing in mice, we have utilized Mus spretus as a model species because it has telomere lengths of approximately the same length as humans. Telomere length and telomerase were analyzed from liver, kidney, spleen, brain and testis from >180 M.spretus male and female mice of different ages. Although telomere lengths for each tissue were heterogeneous, significant changes in telomere lengths were found in spleen and brain, but not in liver, testis or kidney. Telomerase activity was abundant in liver and testis, but weak to nondetectable in spleen, kidney and brain. Gender differences in mean terminal restriction fragment length were discovered in tissues from M.spretus and from M.spretus × C57BL/6 F1 mice, in which a M.spretus-sized telomeric smear could be measured. The comparison of the rank order of tissue telomere lengths within individual M.spretus showed that certain tissues tended to be longer than the others, and this ranking also extended to tissues of the M.spretus × C57BL/6 F1 mice. These data suggest that telomere lengths within individual tissues are regulated independently and are genetically controlled.